基督教的末世论的本体论地位 - 隗仁莲; 安希孟 (中国基督教研究（ISSN：3068-479X）, 2023)
Chapter  V , The  Question  of an Eschatological  Ontology, in The  Logic   of  Promise in Moltmann's  Theology, Christopher  Morse, Philadelphia Fortress  Press, 1979.